PENGARUH INTENSITAS KOMPETISI DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA ORGANISASI DENGAN KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Asuransi di Kota Pekanbaru) - Nicky Fiolita; Desmiyawati -; Rizka Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study examine the effect of intensity of competition, perceipt environmental uncertainty of organizatinal performance which is mediated by the characteristics of management accounting information systems as mintervening variable. The populationwas all the insurance companies in Pekanbaru. The sample of this research was the manager of an insurance company with a sample size of 53 managers. Collection method in this study was a survey method. Method of data analysis used to test the quality of data that includes validity, reliability, and hypothesis testing was the analysis of structural equation modeling (SEM) using software SmartPLS. Hypothesis testing using Partial Least Square test showed that variables influence the intensity of competition, perceipt environmental uncertainty, the characteristics of management accounting information systems affected the organizational performance. The intensity of competition affect the organizational performance with the characteristics of management accounting information system as mediating variable. perceipt environmental uncertainty does not directly affect the organizatinal performance with the characteristics of management accounting information systems as mediating variable. Value of R.Square indicstes that jointly variables influence the intensity of competition, the uncertainty of the environment, the characteristics of management accounting information systems affected the organizational performance. Giving contribution to the dependent variable (organizational performance) of 65.94 % while the remaining 34.06% is explained by other variables outside the model study.Keywords: intensity of competition, perceipt environmental uncertainty, organizatinal performance, characteristics of management accounting information systems.